Evaluation of plusoptiX Photoscreening During Examinations of Children with Autism. (June 2013) - Singman, Eric; Matta, Noelle; Fairward, Amber; Silbert, David
Abstract Purpose: We evaluated the reliability of the the plusoptiX photoscreener compared to a standard pediatric eye exam offered to children with autism. Methods: This is a retrospective chart review of children diagnosed with autism seen at one pediatric ophthalmology practice. Results: Twenty-five children were evaluated. The plusoptiX was found to have a sensitivity of 88% and a specificity of 87% in identifying amblyopia risk factors based on the current American Association for Pediatric Ophthalmology and Strabismus referral criteria. Conclusion: Pediatric vision screening can be especially challenging in children with autism. Minimizing the need for examinations in these children is important. While the plusoptiX does not perform as well when applied to children with autism as it does when offered to children in the general population, it is still a useful tool.